Material-Technical Base Of The Cotton Industry In the Surkhandarya Region In The Second Half Of The 20th Century (The Peerian Journal, 2026)
This article provides a comprehensive scientific-academic analysis of the formation, development, and contradictory consequences of the material-technical base of the cotton industry in the Surkhandarya region during the second half of the 20th century (1950–1991). The study covers the regional characteristics of Soviet agrarian policy, the expansion of irrigation infrastructure, the level of mechanization, the establishment of cotton ginning plants, transport and energy supply, as well as the reforms implemented during the years of independence. Based on archival sources, statistical data, and scholarly literature, the article assesses the materialtechnical potential of the region’s cotton industry and demonstrates the economic consequences of its development dynamics.